A Neurospora crassa osmotic-sensitive mutant showing growth influenced by temperature, light and dark - S. Brown; S. N. Bennett; W. A. Krissinger (Fungal Genetics Reports, 1988)
A Neurospora crassa osmotic-sensitive mutant showing growth influenced by temperature, light and dark